Visible light-induced mono-bromination of arenes with BrCCl3. Issue 48 (24th May 2021) - Fan, Jiali; Wei, Qiancheng; Zhu, Ershu; Gao, Jing; Cheng, Xiamin; Lu, Yongna; Loh, Teck-Peng
Abstract : We reported a highly efficient and regioselective photocatalytic bromination of electron-rich arenes and heteroarenes using commercially available BrCCl3 as a "Br" source. Abstract : A highly efficient and regioselective bromination of electron-rich arenes and heteroarenes using commercially available BrCCl3 as a "Br" source has been developed. The reaction was performed in air under mild conditions with photocatalyst Ru(bpy)3 Cl2 · 6H2 O, avoiding the usage of strong acids and strong oxidants. Mono-brominated products were obtained with medium to excellent yields (up to 94%). This strategy has shown good compatibility and high para -selectivity, which will facilitate the complicated synthesis.